Mining human interactions to construct a virtual guide for a virtual fair - Luna, Andrés Ignacio (2014)
Ponencia presentada en la 14th Conference of the European Chapter of the Association for Computational Linguistics. Workshop on Dialogue in Motion. Gotemburgo, Suecia, 26 de abril de 2014.